'It's like a problem that doesn't exist': The emotional well-being of mothers caring for a child with brain injury. (August 2013) - Jordan, Joanne; Linden, Mark A.
Abstract Background: Although research has shown that significant burden and adverse psychological impact are associated with caring for a child with brain injury, limited knowledge exists concerning the qualitative experience and impact of this burden. Objective: To provide an account of the experiences of mothers who care for a childhood survivor of brain injury. Research design: Postal survey. Methods and procedures: A self-report questionnaire was sent to a consecutive sample of mothers (n = 86) of children (aged 2–28) with acquired brain injury, registered with a UK children's brain injury charity. Five essay style questions enabled mothers to reflect on and describe at length their caring experiences, with particular emphasis placed on the perceived impact on emotional well-being. Main outcomes and results: Thematic analysis identified five key themes: Perpetually Anxious, The Guilty Carer, The Labour of Caring, A Self-Conscious Apologist and Perpetually Grieving. Collectively, these themes highlight two core processes shaping mothers' caring experiences and concomitant mental well-being. First, the collective and enduring nature of caregiver burden over time. Second, the crucial role played by socio-cultural values in perpetuating caregiver burden. Conclusions: Societal norms, particularly those relating to the nature and outcome of brain injury and motherhood, serve to marginalize mothers and increase feelings of isolation. Findings suggest the value of peer support programmes as an effective means of providing appropriate social support.